An Alternative History of Hyperactivity : Food Additives and the Feingold Diet. - Smith, Matthew, 1973- (Critical issues in health and medicine., 2011)
An Alternative History of Hyperactivity explores the origins of the Feingold diet, revealing why it became so popular, and the ways in which physicians, parents, and the public made decisions about whether it was a valid treatment for hyperactivity. Arguing that the fate of Feingold's therapy depended more on cultural, economic, and political factors than on the scientific protocols designed to test it, Smith suggests the lessons learned can help resolve medical controversies more effectively.